The connexin43-interacting protein, CIP85, mediates the internalization of connexin43 from the plasma membrane. (August 2013) - Cochrane, Kimberly; Su, Vivian; Lau, Alan F.
Abstract: CIP85 was previously identified as a connexin43 (Cx43)-interacting protein that is ubiquitously expressed in multiple mammalian tissues and cell types. The interaction between the SH3 domain of CIP85 and a proline-rich region of Cx43 has previously been associated with an increased rate of Cx43 turnover through lysosomal mechanisms. This report presents biochemical and immunofluorescence evidence that overexpression of CIP85 reduced the presence of Cx43 in gap junction plaques at the plasma membrane. Furthermore, this effect was dependent upon the interaction of CIP85 with Cx43 at the plasma membrane. These results indicate that CIP85 increases Cx43 turnover by accelerating the internalization of Cx43 from the plasma membrane. CIP85 was also observed to interact with clathrin, which suggested a role for CIP85 in the clathrin-mediated internalization of Cx43.